TANTANGAN PEMIKIRAN NEO-MODERNISME NURCHOLISH MADJID TERHADAP PEMIKIRAN DAN KEHIDUPAN KEAGAMAAN ISLAM DI INDONESIA - Tina Amelia (ISSUE: Journal of Islamic Studies for Universal Dialogue, 2025)
Neo-modernism is a pattern of thought that attempts to combine modern thinking with traditional thinking. Through the idea of neo-modernism, Nurcholish Madjid offers a renewal of Islamic thought that emphasizes the relevance of religion in modern life without abandoning Islamic values. Of course, the thought of neo-modernism has received a lot of opposition from people who view that traditional Islamic teachings should not be or be updated because of modernity, apart from that there are external problems that come from the Western world which always considers Islam inferior, namely as an irrational religion, therefore neo-modernism Modernism is a discourse or study that needs to be studied to see in full the problems and dynamics mentioned previously. In this paper, the author uses qualitative research methods by collecting library data in the form of data from primary sources, namely the works of Nurcholish Madjid. along with secondary data in the form of sources written by other researchers. The result of this article is Nurcholish Madjid’s thoughts regarding neo-modernism. Experiencing several challenges in relation to life and religious thought, namely: 1. Opposition by some intellectuals and society as controversial, 2. Stagnant religious thought in life, 3. Not being able to differentiate between religion and non-religion in life, 4. Society tends to find it difficult to accept change and concepts that are less grounded. However, the challenge to this thinking actually becomes an opportunity to enrich Islamic courses in Indonesia regarding neo-modernism and the thoughts of Nurcholish Madjid.